Analysis of Factors Affecting Air Pollution Levels Using the Three-Way Analysis of Variance Method - Anggina Sandy Sundari; Amalia Kusumawati; Dino Rimantho (Universitas Muhammadiyah Purwokerto, 2025)
Nowadays, air pollution is a major cause of worsening environmental quality around the world, impacting human health. In Jakarta, once the world's most polluted city, motor vehicle emissions are a major contributor to the increase in PM2.5 concentrations, which are particulate matter harmful to health. This study aims to analyze the factors that affect PM2.5 concentration, analyze the interaction between these factors, and analyze the most influential factor on PM2.5 concentration using the Three-Way ANOVA method. The factors analyzed include weather (rainy and sunny), wind speed (weak wind and moderate wind), and data collection time (morning, afternoon, evening). The results of the analysis showed that the weather variable and data collection time had a significant influence on PM2.5 concentrations in the air, while the wind speed variable did not show a significant influence. In addition, there was no interaction between the independent variables. The data collection time variable has the most dominant influence with an F-count value of 145.80, indicating that PM2.5 concentrations vary more depending on the time of data collection.